Question #9fafb

1 Answer
Jul 5, 2017

y = 5, x = -3

Explanation:

First, you need to remove a variable. Let's choose to get rid of x to solve for y in this case. Notice that if we multiply -2x + 4y = 26 by 3, we can get rid of the x variables:

6x + 5y = 7
3(-2x + 4y = 26) = -6x + 12y = 78

We add the two equations:
6x + 5y = 7
-6x + 12y = 78

Which we'll get 17y = 85

Divide both sides by 17 and we get y = 5

Then we choose one of two original equations to solve for x. Let's choose 6x + 5y = 7

So plugging in y, we get 6x + 5(5) = 7

Then we solve for x, so we get 6x = -24

Divide by 6 for both sides and x = -4

You can double check if x = -4, y = 5 is correct by plugging those two into the second equation, -2x + 4y = 26